2020
DOI: 10.1186/s12917-020-02664-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of interventional animal experiments in Chinese journals: compliance with ARRIVE guidelines

Abstract: Background In view of the inadequacy and incompleteness of currently-reported animal experiments and their overall poor quality, we retrospectively evaluated the reporting quality of animal experiments published in Chinese journals adhering to the Animal Research: Reporting of In Vivo Experiments (ARRIVE) guidelines. Results The databases CNKI, WanFang, VIP, and CBM were searched from inception until July 2018. Two appropriately-trained reviewers s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In the present study, most articles published in both the journals mentioned the disease/pathology studied, whereas only about half the studies (45.76% and 56.86% in the Indian and the international journal, respectively) mentioned details about the experimental model. According to a study conducted in China by Zhao et al, 41% of studies did not state the hypothesis or objective of the study as well as the number of animals used in the study [ 13 ]. For research studies including animal research, providing sample size information with calculation is very crucial as, if a researcher selects a smaller number of animals, it may lead to missing any significant difference even if it exists in population and if more number of animals selected then it may lead to unnecessary wastage of resources and may lead to ethical issues [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, most articles published in both the journals mentioned the disease/pathology studied, whereas only about half the studies (45.76% and 56.86% in the Indian and the international journal, respectively) mentioned details about the experimental model. According to a study conducted in China by Zhao et al, 41% of studies did not state the hypothesis or objective of the study as well as the number of animals used in the study [ 13 ]. For research studies including animal research, providing sample size information with calculation is very crucial as, if a researcher selects a smaller number of animals, it may lead to missing any significant difference even if it exists in population and if more number of animals selected then it may lead to unnecessary wastage of resources and may lead to ethical issues [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there are underlying reasons common to all animal studies for limited compliance to the guidelines, country-, animal model-, or disease-specific factors should also be considered. For this reason, there are many studies in the literature in which publications from different countries and on various animal models were evaluated for compliance to the ARRIVE guidelines [10,[12][13][14]21]. Turkey has made a significant progress in scientific publishing in recent years and has become the source of an increasing number of biomedical journals and publications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, reporting quality of the literature should be continuosly monitored in order to take effective measures to ensure transparency of animal research [9]. The studies evaluating the reporting quality of animal studies have been published on the basis of country, discipline, or animal model [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown 23–27 that medical research reporting guidelines are one of the important means to effectively improve the quality of the medical research. Among them, the PRISMA (preferred reporting items for systematic reviews and meta‐analysis) statement 28 is the current accepted reporting guideline for the systematic review of this study type.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] It is well established that only high-quality studies are likely to be well guided for their clinical translation, which requires not only rigorous design and implementation but also a thorough and standardized reporting. 22 An increasing number of studies have shown [23][24][25][26][27] that medical research reporting guidelines are one of the important means to effectively improve the quality of the medical research. Among them, the PRISMA (preferred reporting items for systematic reviews and metaanalysis) statement 28 is the current accepted reporting guideline for the systematic review of this study type.…”
Section: Introductionmentioning
confidence: 99%